Evaluation of the Drainage System on Jalan Gunung Guntur, Harjamukti District, Cirebon City - Ajeng Nanda Pitriani; Ohan Farhan (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
Residential drainage systems play a crucial role in controlling rainwater runoff to prevent localized flooding and puddles. The development of residential areas along Jalan Gunung Guntur, Harjamukti District, Cirebon City, has led to significant changes in land use, resulting in increased surface runoff. Based on field observations, this area frequently experiences puddles during medium- to high-intensity rainfall. This phenomenon is suspected to be caused by inadequate drainage channel capacity, sedimentation, and lack of routine maintenance. This study aims to determine rainfall intensity and design flood discharge based on the time of concentration, evaluate the capacity of existing drainage channels, and identify the causes of puddle formation. The research method employed is a quantitative descriptive approach with hydrological and hydraulic analyses. The hydrological analysis includes calculating design rainfall, rainfall intensity, time of concentration, and flood discharge using the rational method. Hydraulic analysis is conducted to determine the channel cross-sectional capacity using the Manning formula. The evaluation results indicate that several existing drainage channels are unable to accommodate the runoff discharge occurring within a specific return period, potentially causing puddle formation. Therefore, redesigning or normalizing the channel dimensions is necessary to increase capacity, ensuring the optimal functioning of the drainage system and minimizing the risk of flooding.